Have Academics’ Citation Patterns Changed in Response to the Rise of World University Rankings? A Test Using First-Citation Speeds - Lee, Soo Jeung; Schneijderberg, Christian; Kim, Yangson; Steinhardt, Isabel (Sustainability)
Academics may actively respond to the expectations of the academic status market, which have largely been shaped by the World University Rankings (WURs). This study empirically examines how academics’ citation patterns have changed in response to the rise of an “evaluation environment” in academia. We regard the WURs to be a macro-level trigger for cementing a bibliometric-based evaluation environment in academia. Our analyses of citation patterns in papers published in two higher education journals explicitly considered three distinct periods: the pre-WURs (1990–2003), the period of WURs implementation (2004–2010), and the period of adaption to WURs (2011–2017). We applied the nonparametric Kaplan–Meier method to compare first-citation speeds of papers published across the three periods. We found that not only has first-citation speed become faster, but first-citation probability has also increased following the emergence of the WURs. Applying Cox proportional hazard models to first-citation probabilities, we identified journal impact factors and third-party funding as factors influencing first-citation probability, while other author- and paper-related factors showed limited effects. We also found that the general effects of different factors on first-citation speeds have changed with the emergence of the WURs. The findings expand our understanding of the citation patterns of academics in the rise of WURs and provide practical grounds for research policy as well as higher education policy.
Keywords: world university rankings; citation; first-citation speed; Minerva; Studies in Higher Education

Digitalisation in Agriculture: Knowledge and Learning Requirements of German Dairy Farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal for Research in Vocational Education and Training)
Purpose: This study aims at investigating how digitalisation (in the sense of industry 4.0) has changed the work of farmers and how they experience the changes from more traditional work to digitalised agriculture. It also investigates what knowledge farmers require on digitalised farms and how they acquire it. Dairy farming was used as domain of investigation since it, unlike other industries, has strongly been affected by digitalisation throughout the last years. Method: Exploratory interviews with 10 livestock farmers working on digitalised dairy farms were analysed using qualitative content analysis. A deductive and inductive coding strategy was used. Findings: Farming work has changed from more manual tasks towards symbol manipulation and data processing. Farmers must be able to use computers and other digital devices to retrieve and analyse sensor data that allow them to monitor and control the processes on their farm. For this new kind of work, farmers require elaborated mental models that link traditional farming knowledge with knowledge about digital systems, including a strong understanding of production processes underlying their farm. Learning is mostly based on instructions offered by manufacturers of the new technology as well as informal and non-formal learning modes. Even younger farmers report that digital technology was not sufficiently covered in their (vocational) degrees. In general, farmers emphasises the positive effects of digitalisation both on their working as well as private life. Conclusions: Farmers should be aware of the opportunities as well as the potential drawbacks of the digitalisation of work processes in agriculture. Providers of agricultural education (like vocational schools or training institutes) need to incorporate the knowledge and skills required to work in digitalised environments (e.g., data literacy) in their syllabi. Further studies are required to assess how digitalisation changes farming practices and what knowledge as well as skills linked to these developments are required in the future.
Keywords: Work-Based Learning; Organisational Change; Digital Competences; Qualitative Research; Digitalisation; Farming; Dairy; VET; Vocational Education and Training

Das Praxissemester aus der Perspektive von Mentor*innen: Aufgaben der Lernorte und wahrgenommene Veränderungsbedarfe - Caruso, Carina; Goller, Michael (Lehrerbildung auf dem Prüfstand)
Mentor*innen unterstützen Studierende u.a. bei der Planung, Durchführung und Reflexion von Unterricht. Obwohl Mentor*innen ein hoher Einfluss auf die Professionalisierung angehender Lehrkräfte zugeschrieben wird, gibt es nur wenige Studien, in denen die Perspektive von Mentor*innen beforscht wird. Dieser Beitrag zielt darauf, die Perspektive von Mentor*innen zu den Aufgaben der am Praxissemester beteiligten Lernorte sowie Veränderungsbedarfe zu explorieren. Hierzu werden Ergebnisse einer Interviewstudie mit 23 Mentor*innen vorgestellt, die zur Beantwortung nachstehender Forschungsfragen beitragen: (1) Welche Aufgaben haben die am Praxissemester beteiligten Lernorte und die dort tätigen Akteur*innen hinsichtlich der Vorbereitung, Unterstützung und Begleitung der Studierenden im Praxissemester aus Perspektive befragter Mentor*innen? (2) Was sind aus Sicht von Mentor*innen Veränderungsbedarfe hinsichtlich der Rahmenbedingungen bzw. Konzeption des Praxissemesters? Ein zentraler Befund der Studie ist, dass allen Lernorten attribuiert wird, dass diese Studierende auf die praktische Unterrichtstätigkeit vorbereiten sollen. Die Relevanz der Universitäten wird dabei allerdings als gering eingeschätzt. Auch theoretisch-reflexive Aspekte spielen in den Aussagen der meisten Mentor*innen keine Rolle. Veränderungsbedarf wird von den Mentor*innen vor allem in der Rolle des Zentrums für schulpraktische Lehrerausbildung und der Universität gesehen. Diese Befunde werden anschließend kritisch diskutiert.
Keywords: Lehrerbildung; Mentoring; Praxissemester; Professionalisierung / internship; mentoring; professionalisation; teacher education

Zur Relevanz von Fallarbeit - Caruso, Carina; Woppowa, Jan (Religionspädagogische Beiträge. Journal for Religion in Education)
Der Beitrag verbindet die Sichtweisen verschiedener Professionalisierungsansätze mit der Frage nach der Gestaltung der (universitären) Begleitung angehender Lehrkräfte im Praxissemester. Dabei wird der Wert von Fallarbeit herausgearbeitet und beschrieben, wie eine Unterstützung angehender (Religions-)Lehrkräfte gestaltet sein müsste, um Entwicklung und Lernen im Praxissemester systematisch zu begleiten. Der Beitrag widmet sich daher zuerst den Rahmenbedingungen und Forschungsbefunden zu Langzeitpraktika und der Gestalt von Professionalisierung durch Praxis. Daran schließen sich Denkfiguren zur Unterstützung (religionspädagogischer) Professionalisierungsprozesse von angehenden Lehrkräften im Schulpraktikum durch rekonstruktive Fallarbeit an, aus Sicht etablierter Professionalisierungsansätze.
Keywords: Fallarbeit; Praxissemester; Professionalität; Professionalisierung; Lehrerinnen- und Lehrerbildung / casework; teacher education; internship; professionalization; professionalism

Exploring the impact of pre-service science teachers’ reflection skills on the development of professional knowledge during a field experience - Kulgemeyer, Christoph; Kempin, Maren; Weißbach, Anna; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (International Journal of Science Education)
Keywords: Education

Students in the spotlight: Using collaborative autoethnography to build a community of learning in the Corona crisis - Steinhardt, Isabel (ISA Pedagogy Series)
Due to the Corona crisis, German Higher Education Institutions had to close their campuses in March and lecturers had to teach online. To understand how the Corona crisis affected students, first this article explains the structural and social inequalities in the German higher education system, using Tinto's (1975; 1997) student engagement theory. Second, the concept of Bergman-Rosamond et al. (2020) is used to analyze the challenges that Corona has raised for students, including current surveys. We found that the closure of the social space campus (and the Corona crisis as a whole) particularly hit hard those students who had previously been affected by (intersectional) inequality. Therefore, to lessen the specific challenges associated with the ad hoc transition to digital studying, the creation of a digital community of learning can help. We demonstrate how such a community can be created by the example seminar, "Digital practices: an autoethnographic observation". During the seminar, students recorded their digital technology use in a journal, and we analyzed the diary entries using the collaborate autoethnography method. The seminar example shows that this method is well suited for the development of a community of learning as it not only places students in the spotlight but as students work together on a topic they get to know each other, and a basis of trust is created through peer-feedback. Therefore, it was important to have a digital space (in this case Mahara) where the exchange could take place. The continuous insight into the students’ "learning status" enabled the lecturer to promote the learning and provide individual assistance for the students.
Keywords: Intersectionality; inequality; gender; diversity; higher-education; crisis

Kompetenzdiagnose in der Berufsbildung von Pflegelehrpersonen - Schürmann, Mirko; Bender, Elena; Grebe, Christian (Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO))
Zusammenfassung In diesem Beitrag der Zeitschrift Gruppe. Interaktion. Organisation. (GIO) wird das Instrument zur Diagnose pädagogischer Kompetenzen von Pflegelehrpersonen (PädKomPflege) vorgestellt. Die Berufsbildung in der Pflege ist durch sich verändernde inhaltliche und gesetzliche Anforderungen geprägt. Verschiedene landesspezifische rechtliche Vorgaben führen zu einem sehr heterogenen Bild von Qualifikationen und Kompetenzen der Pflegelehrpersonen. Die Anrechnung bereits erworbener Kompetenzen auf pflegepädagogische Studiengänge sowie die Kompetenzerfassung und -bilanzierung in Berufsbildungseinrichtungen spielt daher eine wichtige Rolle. Vor diesem Hintergrund wurde das Instrument PädKomPflege entwickelt und erprobt. Grundlage des Kompetenzmodells sind die Empfehlungen der Kultusministerkonferenz (2004) zu den Standards für die (allgemeine) Lehrerbildung sowie Expertenworkshops und -interviews mit PflegedidaktikerInnen. Die empirische Erprobung erfolgte an einer Stichprobe von 1096 Pflegelehrpersonen. Psychometrische Analysen auf Grundlage der klassischen Testtheorie sowie IRT-basierte Analysen führten zu einer Überarbeitung des Instruments, welches nun als zweisprachiges Online-Self-Assessmenttool (eng./deut.) vorliegt. Die Validierung der deutschsprachigen Version fand anhand von 545 TeilnehmerInnen im Jahr 2016 statt, sodass ein geprüftes Instrument mit 54 Items in den fünf Hauptskalen (Unterricht, Beurteilung, Beratung, Lernortkooperation sowie Organisations- und Schulentwicklung) und 18 Subskalen zur Verfügung steht. Sowohl klassische als auch probabilistische Testgütekriterien werden erfüllt. Die Skalen weisen hohe interne Konsistenzen auf ( α > 0,80) und sind überwiegend konstruktvalide. So lassen sich für 17 der 18 Subskalen ordinale Raschmodelle anpassen. Auf der Ebene der Hauptskalen können Partial Credit Modelle für alle Items von modellkonformen Subskalen einer Hauptskala angepasst werden. Das Instrument kann zur individuellen Kompetenzdiagnostik, zur Identifikation von Bildungsbedarfen in Schulen des Gesundheitswesens und im Kontext beruflicher Bildungsprozesse genutzt werden. In der Onlineversion erhalten Teilnehmende abschließend ein individuelles Kompetenzprofil mit möglichen Vergleichswerten. Das Tool kann begleitend zu Qualifizierungsprozessen als Monitoring-Instrument oder zur individuellen Kompetenzbilanzierung eingesetzt werden.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology; Developmental and Educational Psychology; Education; Social Psychology

Regulating Transitions from School to Work. An Institutional Ethnography of Activation Work in Action - Dahmen, Stephan
How are activation programs for the young unemployed implemented? How do street-level bureaucrats deal with competing rationalities and demands for action? Transition policies increasingly aim at promoting self-regulation and constructing employable subjects. Stephan Dahmen explores the practical regulation of biographical transitions in activation programs for the young unemployed by focusing on the interactive accomplishment of activation work. The study reveals how the critical tensions of activation policies are continually re-interpreted and adapted to local contingencies and describes the various organisational technologies used for creating employable subjects.
Keywords: Youth; Welfare State; Transitions; Human Service Organizations; Institutional Ethnography; Activation; Sociology of Conventions; Work; Education; Educational Research; Sociology of Education; Social Pedagogy; History of Education; Bielefeld University Press

Regulating Transitions from School to Work. An Institutional Ethnography of Activation Work in Action - Dahmen, Stephan
How are activation programs for the young unemployed implemented? How do street-level bureaucrats deal with competing rationalities and demands for action? Transition policies increasingly aim at promoting self-regulation and constructing employable subjects. Stephan Dahmen explores the practical regulation of biographical transitions in activation programs for the young unemployed by focusing on the interactive accomplishment of activation work. The study reveals how the critical tensions of activation policies are continually re-interpreted and adapted to local contingencies and describes the various organisational technologies used for creating employable subjects.
Keywords: Youth; Welfare State; Transitions; Human Service Organizations; Institutional Ethnography; Activation; Sociology of Conventions; Work; Education; Educational Research; Sociology of Education; Social Pedagogy; History of Education; Bielefeld University Press

Digitally Assessing Text Comprehension in Grades 3-4: Test Development and Validation - Seifert, Susanne; Paleczek, Lisa (Electronic Journal of e-Learning)
A prerequisite for child reading support at school is adequate assessment. Embedding (repeated) assessment into daily teaching routine is often challenging for teachers in terms of time and organization. The use of digital tools can help teachers in the assessment process (in preparation, evaluation, documentation, etc.). A digital assessment tool (Graz Reading Comprehension test: GraLeV), focusing on assessing reading comprehension skills in Grades 3 and 4 is currently being developed in Austria. This reading assessment covers reading comprehension at the word, sentence, and text level. Text level is assessed via two subtests (Subtest I: presentation of nonsense-stories and corresponding questions, and Subtest II: maze selection). The other levels consist of one subtest each. This paper focusses on the subtests at text level. More specifically, the paper reports the results of two studies. Study 1 describes the development phases and the first piloting of these two subtests (data collection: 10/2019-12/2019). Testing 273 students with preliminary versions of the subtests (Subtest I: 30 items, Subtest II: 60 items) produced information on (a) item difficulty, (b) item discriminatory power, and (c) time limits for future speed testing. Items not meeting the required quality criteria were excluded. The final version of Subtest I consists of 16 questions referring to eight different, short, nonsense-texts. Its testing time (without instructions) is three minutes. The final version of the Subtest II consists of 2 texts each with 15 maze selections (30 items) and testing time is 100 seconds. The internal consistency is found to be good for Subtest I (α=.87) and Subtest II (α=.78 to .80). Study 2 reports on testing for validity and retest-reliability (data collection: 09/2020-11/2020). Student scores in another reading comprehension test, together with teacher assessments of reading comprehension, were used to assess congruent validity. Divergent validity was assessed using teacher assessments of mathematical and socio-emotional skills. As expected, the correlations with the congruent measures were higher than those with the divergent measures. A subsample was tested twice with the GraLeV. Retest-reliability was acceptable for Subtest II. However, the scores obtained at time 2 were higher compared to those at time 1 in both subtests. This is probably the result of increased student familiarity with the digital device and the digital test environment at time 2. The results are discussed in the light of teachers’ needs for standardized digital assessments in order to facilitate the tailoring of student reading support.
Keywords: Computer Science Applications; Education